2006
DOI: 10.1590/s1516-89132006000700008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of proteins from the red seaweed Hypnea musciformis (Wulfen) Lamouroux on the growth of human pathogen yeasts

Abstract: A protein fraction, rich in lectin, obtained from the red seaweed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 31 publications
0
19
0
1
Order By: Relevance
“…Most of them are based on the effects of linear β-1,3 glucans and its induction to the release of H 2 O 2 in tobacco leaves (Klarzynski et al 2000). Jayaraman et al (2011) also point out the extract ability to enhance various defenserelated enzymes including β-1,3 glucanase known to be present in red algae having anti-fungal properties (Cordeiro et al 2006). This combined with the extract's hormone-like elicitor activities (mostly cytokinin-like) was already discussed by Reitz & Trumble (1996) and Khan et al (2009) and the presence of betaines demonstrated by Mackinnon et al (2010) and Blunden et al (2009) in Ascophyllum extracts, reported to influence the increase of chlorophyll content by Whapham et al (1993).…”
Section: Discussionmentioning
confidence: 99%
“…Most of them are based on the effects of linear β-1,3 glucans and its induction to the release of H 2 O 2 in tobacco leaves (Klarzynski et al 2000). Jayaraman et al (2011) also point out the extract ability to enhance various defenserelated enzymes including β-1,3 glucanase known to be present in red algae having anti-fungal properties (Cordeiro et al 2006). This combined with the extract's hormone-like elicitor activities (mostly cytokinin-like) was already discussed by Reitz & Trumble (1996) and Khan et al (2009) and the presence of betaines demonstrated by Mackinnon et al (2010) and Blunden et al (2009) in Ascophyllum extracts, reported to influence the increase of chlorophyll content by Whapham et al (1993).…”
Section: Discussionmentioning
confidence: 99%
“…The genus Hypnea is an important source of polysaccharides used as gelling and thickening agents in food and nonfood industries (Andrade et al 2000, Cordeiro et al 2006. In addition to their emulsifying properties, polysaccharides and other metabolites with antibacterial and antitumor properties have been extracted from a number of Hypnea species.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the aqueous extracts of H. japonica, Hypnea musciformis, and Hypnea cervicornis have shown agglutinating activity against native and trypsin-treated rabbit erythrocytes (Ainouz and Sampaio 1991;Hori et al 1986Hori et al , 2000. Two lectins with antifungal and antimicrobial activity have also been isolated from H. musciformis and H. cervicornis (Melo et al 1997;Nagano et al 2005;Cordeiro et al 2006). It has been reported that the polysaccharide fractions from Hypnea charoides show high antiviral activity against type 1 and type 2 HSV, while maintaining low cytotoxicity levels (Smit 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial activity of algae extracts is generally assayed using various organic solvents, such as acetone, ether, chloroform, methanol [44]. An organic solvent always provides a higher efficiency in extracting compounds for antimicrobial activity [45,46].…”
Section: Discussionmentioning
confidence: 99%